Estimation of Regression Coefficients in the Presence of Spatially Autocorrelated Error Terms - Dubin, Robin A. (The Review of Economics and Statistics, 1988)
Spatial autocorrelation occurs when population members are related through their geographic location. This paper presents a maximum likelihood procedure for simultaneously estimating the parameters of the correlation function and the regression coefficients. A test for the presence of spatial autocorrelation is also provided. Estimation of an hedonic regression illustrates the technique. Copyright 1988 by MIT Press.